Validitas Butir Soal Pemahaman Konsep dengan Rasch Model - Musanni, Musanni; Gummah, Syifaul; Ahzan, Sukainil (Jurnal Ilmiah IKIP Mataram, 2023)
The study aims to validity of a pre test of physics by researchers to the XI MIPA SMAN 5 Mataram classes on Newton’s law study material about gravity. The analyzer techniques use rasch’s model’s. the result of a studyon the XI MIPA SMAN 5 Mataram class sample came from 20 preliminary questions presented, 4 invalid problem can be used for research studies on X MIPA SMAN 5 Mataram only 16 problems.